Simultaneous measurement of aliphatic alcohol concentration and temperature based on etched taper FBG - Yang, H.Z.; Qiao, X.G.; Rajibul, I.M.; Lim, K.S.; Ahmad, Harith (Elsevier, 2014)
A broadband fiber Bragg grating based on etch tapering is demonstrated for simultaneous sensing of aliphatic alcohol concentration and temperature. Chemical etching approach is used to produce a decaying exponential shape FBG. A reflection bandwidth of 20.08 nm is obtained when the smallest fiber radius as small as 2.2 μm is achieved. In the analysis, the bandwidth of the reflection spectrum is evaluated for measuring the refractive index whereas the wavelength shift of the resonant peak is evaluated for the temperature change. The experiment results indicate that the proposed sensor has a maximum sensitivity of 428.07 nm/RIU at the RI value of 1.3265, a temperature sensitivity of 9.9 pm/°C, and a bandwidth sensitivity of 0.92 pm/°C is finding at methanol concentration of 10%.